2020
DOI: 10.1534/genetics.120.303459
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Algorithms for Calculating Epistatic Genomic Relationship Matrices

Abstract: The genomic relationship matrix plays a key role in the analysis of genetic diversity, genomic prediction and genome-wide association studies. The epistatic genomic relationship matrix is a natural generalization of the classic genomic relationship matrix in the sense that it implicitly models the epistatic effects among all markers. Calculating the exact form of the epistatic relationship matrix requires high computational load and is hence not feasible when the number of markers is large or when high-degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
1
25
0
Order By: Relevance
“…Moreover, it has been shown that the superiority of epistasis models over the additive GBLUP in terms of predictive ability may vanish when the number of markers increases (Schrauf et al 2020 ). Also, the Hadamard products of the additive genomic relationship matrices provide only an approximation for the interaction effect model based on interactions between different loci (Martini et al 2020 ), and more correcting factors are required for interactions of higher degree (Jiang and Reif 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that the superiority of epistasis models over the additive GBLUP in terms of predictive ability may vanish when the number of markers increases (Schrauf et al 2020 ). Also, the Hadamard products of the additive genomic relationship matrices provide only an approximation for the interaction effect model based on interactions between different loci (Martini et al 2020 ), and more correcting factors are required for interactions of higher degree (Jiang and Reif 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Future improvements will cover the use of epistatic genomic relationship matrix (EGRM) to control for the effect of diversity [29], as well as more advanced visualization approaches using either d3 or Cytoscape JavaScript library for dynamic web-based visualization. We also plan to add an end-to-end integration with cloud-based Random Forest implementation Vari-antSpark [15], to enable epistasis search within the ultra-high dimensional data of whole-genome sequencing cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…sum of the diagonal elements) was equal to the number of animals [ 21 ]. As implied from a study by Vitezica et al [ 21 ] and as illustrated by Jiang et al [ 22 ], the Hadamard product between the corresponding matrices includes the squares of the same SNP and reciprocal products between two SNPs (e.g., SNP A by SNP B and SNP B by SNP A). Thus, for the AA interaction, which was shown to have non-negligible variance components for all traits, we calculated AA avoiding these issues and compared it with AA calculated with the Hadamard product of A .…”
Section: Methodsmentioning
confidence: 99%